The Impact of Gadget Screen Exposure in Children and Developmental Status Aged 12 - 72 Months - Endah Dian Marlina; Raudhatul Munawarah; Rosita Syaripah (GLOBAL HEALTH SCIENCE GROUP, 2026)
In 2023, Indonesia’s population of children under five reached 30.2 million. Current data indicates that 33.44% of early childhood individuals are exposed to digital devices, with many facing risks of psychological, cognitive, and socio-emotional impairments. Objective: This study aims to analyze the relationship between gadget screen exposure and the developmental status of children aged 12–72 months. A quantitative study with a cross-sectional design was conducted at Posyandu Puskesmas Pulo Gadung, East Jakarta, in 2025. A sample of 60 respondents was selected through purposive sampling. Data were collected using the Pre-Screening Developmental Questionnaire (KPSP) and a maternal questionnaire regarding gadget usage. Data were analyzed using univariate and bivariate (Chi-square) analysis. Bivariate analysis revealed a significant relationship between gadget exposure and developmental status (p < 0.05). High gadget exposure was predominantly associated with